OpenLCA data for the evaluation of e-bike and dynamo - Almandoz Forcen, Koldo (Cranfield University, 2023)
Flow, process, product system and project data for OpenLCA modelling of e-bikes with and without dynamo energy harvesting.
Keywords: 'LCA'; 'Cycling'; 'Transportation'; 'Li-Ion battery environmental impact'; 'sustainability assessments'